SLANG EXPRESSION USED BY AUSTRALIAN TOURIST AT SORAKE BEACH SOUTH NIAS REGENCY - Mohamad Yunus Laia; Fran Arventianus Wau (LPPM Universitas Nias Raya, 2022)
English language is devided into two kinds, they are Formal English and Informal English. In the field, Australian people who speak English use the informal English to communicate with their friends depends where they are and in what occasion they speak. And this informal English is called Slang. The purpose of this research was to describe the slang that produced by Australian Tourist at Sorake Beach and to classify the based on the types of slang. This research is focused on three domains, there are beach, surfcamp and shop. Then, this research was designed by using Qualitative Research. The data was taken from the Australian Tourist at Sorake Beach and the informants were seven (7) people. Researcher used Handphone as a tool to record their voices and the video during they speak to their friends. The result of the data shows that, the researcher found fifteen (15) Slang expressions that produced by Australian Tourist at Sorake Beach. Australian does speak and use the slang expressions in the their communication with their friends and they mostly use the Public slang in their communication because they usually drink beers and they stay at the beach. It can be concluded, slang is an informal expression that usually exist in English speaking to make the language more fashionable and attractive. The researcher suggests to the readers to use the result of the research as references to increase their knowledge about English and they can implement this research to communicate with the Australian tourist.